Handbook of energy engineering calculations - Hicks, Tyler Gregory, 1921- (New York : McGraw-Hill, 2012)
"SOLVE ENERGY PROBLEMS QUICKLY AND ACCURATELYFilled with step-by-ste p procedures for performing hundreds of calculations, this practical gu ide helps you solve a variety of applied energy engineering design and operating problems. Handbook of Energy Engineering Calculations feature s worked-out examples and enables you to obtain accurately results with minimum time and effort. Calculation procedures emphasize greenhouse g as and carbon dioxide emissions control as well as energy conservation and reuse. This is an invaluable, time-saving resource for anyone invol ved in energy engineering.Comprehensive coverage includes: Energy conve rsion engineering Steam power generation Gas-turbine power generation I nternal-combustion engine energy analysis Nuclear energy engineering Hy droelectric energy power plants Wind power energy design and applicatio n Solar power energy application and usage Geothermal energy engineerin g Ocean energy engineering Heat transfer and energy conservation Fluid transfer engineering Interior climate control energy economics Energy c onservation and environmental pollution control "--Provided by publishe r.
"This practical guide helps engineers solve energy problems quickly and accurately using step-by-step procedures for performing more than 5 00 calculations together with worked out examples and numerical results "--Provided by publisher.
Energy conversion engineering -- Steam power generation -- Gas-turbi ne energy power generation -- Internal combustion engine energy analyse s -- Nuclear energy engineering -- Hydroelectric energy power plants -- Wind-power energy design and applications -- Solar-power energy applic ation and usage -- Geothermal energy engineering -- Ocean energy engine ering -- Heat transfer and energy conservation -- Fluid transfer engine ering -- Interior climate control energy economics -- Energy conservati on and environmental pollution control. power generation Reciprocating -engine power generation Nuclear power generation Renewable energy sour ces for "green" power generation Sewage and wastewater treatment and re -use in energy options .
Includes index.
Keywords: Power (Mechanics) -- Mathematical models -- Handbooks, manuals, etc; Force and energy -- Mathematical models -- Handbooks, manuals, etc; Engineering mathematics -- Formulae -- Handbooks, manuals, etc